2013
DOI: 10.1186/ar4243
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis and the pathogenesis of rheumatoid arthritis: analysis of various compartments including the synovial tissue

Abstract: IntroductionWe evaluated the presence of Porphyromonas gingivalis (Pg) DNA in the synovial tissue through synovial biopsy and in other compartments of rheumatoid arthritis (RA) patients in comparison with patients affected by other arthritides. Possible links with clinical, immunologic and genetic features were assessed.MethodsPeripheral blood (PB), sub-gingival dental plaque, synovial fluid (SF) and synovial tissue samples were collected from 69 patients with active knee arthritis (32 with RA and 37 with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 27 publications
1
45
0
3
Order By: Relevance
“…Using that technique, we were able to confirm the presence of P. gingivalis DNA in ligatures from all 9 challenged animals (Additional file 1: Figure S1a, b). Due to the fact that the presence of P. gingivalis DNA in synovial tissue of patients with active periodontitis have previously been reported [43], we also tested DNA isolated from metacarpophalangeal joint tissue of challenged animals. However, we were not able to detect any traces of P. gingivalis in these samples (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using that technique, we were able to confirm the presence of P. gingivalis DNA in ligatures from all 9 challenged animals (Additional file 1: Figure S1a, b). Due to the fact that the presence of P. gingivalis DNA in synovial tissue of patients with active periodontitis have previously been reported [43], we also tested DNA isolated from metacarpophalangeal joint tissue of challenged animals. However, we were not able to detect any traces of P. gingivalis in these samples (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The oral pathogen P. gingivalis , strongly associated with periodontitis, has been suggested to be involved in the pathogenesis of RA since the presence of P. gingivalis DNA has previously been reported in the synovial tissue of RA patients [43], and since patients with RA have been shown to have higher anti- P. gingivalis and anti-RgpB antibody levels, compared to controls [26, 30]. In the current study, in line with previously reported data [68] P. gingivalis DNA was detected in the oral cavity of the periodontitis-affected animals, although the presence of P. gingivalis in metacarpophalangeal joint tissue of periodontitis-affected animals could not be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis is an anaerobic bacterium (1) that is linked with periodontal disease (2–4) and multiple systemic diseases (5–7). In previous studies (8–11), P. gingivalis strains have shown a variety of pathogenic phenotypes in vitro and in vivo , but underlying genetic mechanisms are poorly defined.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Joint problems have been correlated with oral diseases to our knowledge since the time of Hippocrates, but the association of periodontal disease, and specifically Porphyromonas gingivalis, with rheumatoid arthritis is much more recent [53]. This association is also to date perhaps one of the most studied oral versus systemic chronic disease links [53, 54]. Multiple epidemiologic and clinical studies have found varying relations between periodontal disease and RA [10, 53].…”
Section: Rheumatoid Arthritis and Oral Microbesmentioning
confidence: 99%
“…As players in the etiology of periodontal disease, several oral bacteria have been studied for association with RA etiology. Clinical studies have detected P. gingivalis, Prevotella intermedia , and Prevotella nigrescens DNA in sera and synovial fluids of RA patients [56], and antibodies against P. gingivalis, A. actinomycetemcomitans and few other oral microbiota constituents have also been found in sera of patients suffering from RA, compared to healthy controls [53, 54]. …”
Section: Rheumatoid Arthritis and Oral Microbesmentioning
confidence: 99%